Time series analysis of the NOANET CGPS stations - Chousianitis, K.; Ganas, A.; Papanikolaou, M.; Argyrakis, P.; Drakatos, G.; Makropoulos, K. (Bulletin of the Geological Society of Greece, 2013)
The National Observatory of Athens has begun installing permanent GPS stations on February 2006 including a EUREF permanent station in Attica, NOA1. Currently the National Observatory of Athens operates 20 continuous GPS stations around Greece all sampling at 1-s and transmitting real-time data to Athens. Several stations also sample at 0.2-s (5 Hz) and record the data in the ring buffer for a period of 1-2 days. Their location is carefully selected so that both geological and seismotectonic criteria are fulfilled. All stations are situated close to major seismogenic structures of Greece such as the Cephalonia Transform Fault (CTF) in the Ionian Sea (VLSM, PONT, SPAN, KIPO), and the two North Anatolian Fault branches in the North Aegean Sea (PRKV, LEMN ). We describe the CGPS data archiving and processing procedures, used to combine into a uniform velocity solution the observations of all the NOANET stations, accounting for the seasonal (annual and semiannual) signals, and considering the off-sets in the coordinate time-series.